Economic comparison of two methods of supplementary feeding in Finnish reindeer management - Helle, T.; Walters, C. (Rangifer, 1984)
The most common methods are (1) supplementary feeding with dry hay (maximally 50 kg per head a season) on natural ranges in mid and late winter, and (2) corral feeding, where the reindeer are fed in small yard-corrals with hay, green silage, lichen, molasses and commercial reindeer feeds for 3-5 months a winter.